Encapsulated Food Products as a Strategy to Strengthen Immunity Against COVID-19 - Tripathy, Soubhagya; Verma, Deepak Kumar; Thakur, Mamta; Patel, Ami R.; Srivastav, Prem Prakash; Singh, Smita; Chávez-González, Mónica L.; Aguilar, Cristobal N. (Frontiers in Nutrition, 2021)
In December 2019, the severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) - a novel coronavirus was identified which was quickly distributed to more than 100 countries around the world. There are currently no approved treatments available but only a few preventive measures are available. Among them, maintaining strong immunity through the intake of functional foods is a sustainable solution to resist the virus attack. For this, bioactive compounds (BACs) are delivered safely inside the body through encapsulated food items. Encapsulated food products have benefits such as high stability and bioavailability, sustained release of functional compounds; inhibit the undesired interaction, and high antimicrobial and antioxidant activity. Several BACs such as ω-3 fatty acid, curcumin, vitamins, essential oils, antimicrobials, and probiotic bacteria can be encapsulated which exhibit immunological activity through different mechanisms. These encapsulated compounds can be recommended for use by various researchers, scientists, and industrial peoples to develop functional foods that can improve immunity to withstand the coronavirus disease 2019 (COVID-19) outbreak in the future. Encapsulated BACs, upon incorporation into food, offer increased functionality and facilitate their potential use as an immunity booster. This review paper aims to target various encapsulated food products and their role in improving the immunity system. The bioactive components like antioxidants, minerals, vitamins, polyphenols, omega (ω)-3 fatty acids, lycopene, probiotics, etc. which boost the immunity and may be a potential measure to prevent COVID-19 outbreak were comprehensively discussed. This article also highlights the potential mechanisms; a BAC undergoes, to improve the immune system.